PENGARUH MEDIA INTERAKTIF POWERPOINT DALAM MENINGKATKAN MOTIVASI BELAJAR SISWA KELAS IV SD PERUMNAS 1 - Muhammad Nur Abdullah; Muh. Rheza Syahputra (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2025)
This study focuses on examining the impact of using interactive PowerPoint media on enhancing the learning motivation of fourth-grade students at SD Perumnas 1.The study was initiated due to the low learning motivation observed among students, which is largely attributed to conventional, one-way teaching methods that lack student engagement and active participation. The study employed a quantitative approach with a quasi-experimental design, specifically the one-group pretest-posttest model. A total of 30 fourth-grade students were selected as the sample through purposive sampling. Data collection was carried out using a learning motivation questionnaire administered before and after the intervention, and was further supported by observations and documentation. The data analysis, conducted using a paired sample t-test, revealed a significance value of 0.000 (<0.05), indicating a statistically significant difference in students’ motivation scores before and after the use of interactive PowerPoint media. The average motivation score improved from a moderate to a high category.